The breakpoint of an inversion of chromosome 14 in a T-cell leukemia: sequences downstream of the immunoglobulin heavy chain locus are implicated in tumorigenesis. - Baer, R (1987)
T-cell tumors are characterized by inversions or translocations of chromosome 14. The breakpoints of these karyotypic abnormalities occur in chromosome bands 14q11 and 14q32--the same bands in which the T-cell receptor (TCR) alpha-chain and immunoglobulin heavy chain genes have been mapped, respectively. Patients with ataxia-telangiectasia are particularly prone to development of T-cell chronic lymphocytic leukemia with such chromosomal abnormalities. We now describe DNA rearrangements of the TCR alpha-chain gene in an ataxia-telangiectasia-associated leukemia containing both a normal and an inverted chromosome 14. The normal chromosome 14 has undergone a productive join of TCR alpha-chain variable (V alpha) and joining (J alpha) gene segments. The other allele of the TCR alpha-chain gene features a DNA rearrangement, about 50 kilobases from the TCR alpha-chain constant (C alpha) gene, that represents the breakpoint of the chromosome 14 inversion; this breakpoint is comprised of a TCR J alpha segment (from 14q11) fused to sequences derived from 14q32 but on the centromeric side of C mu. These results imply that 14q32 sequences located at an undetermined distance downstream of the immunoglobulin C mu locus can contribute to the development of T-cell tumors.